Linguistic Attitudes towards Quechua and Spanish of Basic Education Students in Huánuco: a Qualitative Analysis - Ramírez Rodríguez, Lizlaleyne (2022)
The linguistic attitudes of bilingual Quechua-Spanish schoolchildren from the community of Bello Progreso in the province of Huacaybamba in the region of Huánuco are analysed. From the mentalistic theory and the three dimensions: cognitive, affective and behavioural, the subjective, cultural, explicit positive or negative evaluations towards the Quechua and Spanish languages are explained. Likewise, the influence of sociolinguistic traits such as age, school grade, family, and family context are also considered. A descriptive level of research with a qualitative approach is used. The results of the research show that the Spanish language is more highly valued than the Quechua language due to different needs, such as integration into the academic and working world, which leads to the influence of negative attitudes towards the native language. In conclusion, the Spanish language is more highly valued than the Quechua language by bilingual students in a public educational institution.